Production Process of Steam Power Plant and Calculation of Thermal Efficiency: Case Study of Teluk Sirih Steam Power Plant - Putri Pratiwi; Zakil Hadi (Jurnal Teknik Mesin, 2022)
The performance of a power plant can be known from the calculation of efficiency in the generating sector. Steam power plants utilize a series of energy conversion processes including: conversion of chemical energy into thermal energy when extracting heat from coal as fuel to heat boilers, conversion of thermal energy into mechanical energy in turbines and conversion of mechanical energy into electrical energy in generators. Like other steam power plants, the Teluk Sirih PLTU located in Bungus Teluk Kabung, West Sumatra has the same energy production process. it's just that the source of the water is taken from the sea so it requires special treatment to turn the water into water suitable for producing steam used in this power plant. The electricity production process will be explained in this study and an efficiency calculation process with a simple Rankine cycle is carried out to determine the efficiency of this power plant. From the calculation results, the thermal efficiency of PLTU Teluk Sirih is 29%. Based on the results of these calculations, it is known that the Telusk Sirih PLTU can be classified as a power plant with good efficiency.